Forward Modeling and Optimization of Methane Emissions in the South Central United States Using Aircraft Transects Across Frontal Boundaries. Issue 22 (26th November 2019) - Barkley, Z. R.; Davis, K. J.; Feng, S.; Balashov, N.; Fried, A.; DiGangi, J.; Choi, Y.; Halliday, H. S.
Abstract: The South Central United States is a hot spot for anthropogenic methane (CH4 ) emissions, with contributions from the oil/gas (O&G) and animal agriculture sectors. During frontal weather events, airflow combines enhancements from these emissions into a large plume. In this study, we take CH4 and ethane (C2 H6 ) observations from the Atmospheric Carbon and Transport‐America campaign and adjust O&G and animal agriculture emissions such that modeled CH4 and C2 H6 enhancements match the observed plume. Results from the joint CH4 ‐C2 H6 optimization indicate that emissions from the O&G sector are 1.8 ± 0.7 (2 σ ) times larger than EPA inventory estimates. These results match synthesis work from recent literature and reject the possibility that this increase compared to inventories is due to a potential bias in daytime‐only measurements of these facilities. Successful modeling from this study raises the possibility of using trace gas measurements along frontal crossings to solve for emissions in other regions of the United States. Key Points: Methane and ethane observations from U.S. Midwest frontal flights are used to solve for emissions from oil/gas and animal agriculture Methane emissions from oil/gas sectors in the South Central United States are 1.8 ± 0.7 (2 σ ) times larger than U.S. EPA inventory estimates Measurements across frontal structures can provide opportunities to solve for regional emissions of trace gases in other regions